Ergonomics of Safety Design: Research and Implementation: 2002-2024 Bibliometric Analysis - Bayu Yoni Setyo Nugroho; Maria Goretti Catur Yuantari; Ratih Pramitasari; Izzatul Alifah Sifai; Supriyono Asfawi; Chalobon Treesak; Muhammad Ashraf Fauzi (The Indonesian Journal of Occupational Safety and Health, 2026)
Background: Ergonomic assessments in occupational safety and health are primarily based on the method of subjective observation. However, during the past two decades major technological developments have occurred, with the potential to revolutionise ergonomic evaluation methods. Methods: This bibliometric study was conducted to systematically map studies on safety design ergonomics between 2002 and 2024. Out of an initial pool of 225 articles all of them were carefully selected and analysed using VOSViewer in order to examine publication trends, geographic distribution, and the evolution of key themes. Results: Notable innovations include wearable sensors to capture real-time posture, Microsoft Kinect to record movement and automated assessments using artificial intelligence, fuzzy logic and machine learning. The advent of Industry 4.0 has led to the development of Motion Analysis Systems and digital twin technologies which encourage human-robot collaboration. The emergence of collaborative robots and exoskeletons offers encouraging ways to prevent musculoskeletal disorders. Most of the research is concentrated in developed countries with many of the findings published in interdisciplinary journals. Conclusion: This bibliometric analysis indicates the rapid growth in the use of AI-enabled and sensor-based ergonomic assessment tools, especially since 2018. The results indicate a shift towards ergonomics adapted for workplaces, which was not emphasised in previous studies. The successful implementation of such technologies requires addressing issues concerning costs, developing standardised procedures, and ensuring equitable access.